2019
DOI: 10.1002/smll.201902222
|View full text |Cite
|
Sign up to set email alerts
|

α‐Ni(OH)2 Originated from Electro‐Oxidation of NiSe2 Supported by Carbon Nanoarray on Carbon Cloth for Efficient Water Oxidation

Abstract: wide applications are highly restricted by their low abundance and high cost. [7][8][9] In recent years, tremendous research efforts have been devoted to developing earthabundant, low-cost, and highly-efficient OER electrocatalysts, among which transition metal based compounds including transition metal oxides, [10][11][12] hydroxides, [13][14][15][16][17][18] phosphides, [19,20] sulfides, [21,22] and selenides [23][24][25] have been demonstrated to have favorable electrocatalytic property and durability. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…The structural reconstruction of the pre-catalyst is a slow process that has been verified using operando XAFS in our previous studies that involved NiS 2 and NiSe 2 . 11,15 According to the chronopotentiometry results, the measured potential increased gradually during the initial stage (0 to 1–2 hours), which could be ascribed to the phase transition from NiS 2 /NiSe 2 /Ni 5 P 4 to Ni(OH) 2 (Fig. S7, ESI†).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The structural reconstruction of the pre-catalyst is a slow process that has been verified using operando XAFS in our previous studies that involved NiS 2 and NiSe 2 . 11,15 According to the chronopotentiometry results, the measured potential increased gradually during the initial stage (0 to 1–2 hours), which could be ascribed to the phase transition from NiS 2 /NiSe 2 /Ni 5 P 4 to Ni(OH) 2 (Fig. S7, ESI†).…”
Section: Resultsmentioning
confidence: 96%
“…The full transformations of anion-regulated pre-catalysts into NiOOH were proven in our previous work. 11,15 Yan et al also reported that Co 9 S 8 would be fully reconstructed into CoOOH during the OER process. 22 Here, it should be noted that our findings were different from the previous partially reconstructed NiOOH systems, such as the formation of the coreshell structure, 12,13 the residual anion atoms residing on the surface lattice oxygen sites, 14 etc.…”
Section: Papermentioning
confidence: 99%
“…In addition to specific peaks of the ZnP NRs, some peaks locate at 40.7°, 47.3°, 54.2°, and 66.5° are attributed to the (111), (210), (300), and (310) crystal planes of Ni 2 P phase (JCPDS #65-9706). [31] Meanwhile, other peaks appear at 30.0°, 33.7°, 36.9°, 42.9°, 45.3°, 50.7°, 55.6°, 57.9°, and 62.2° are associated with the (200), (210), (211), (220), ( 221), (311), (230), (321), and (400) crystal planes of NiSe 2 phase (JCPDS#11-0552), [32] validating the formation of Ni 2 P-NiSe 2 shell, fully consistent with the TEM observations. Crystalline features of the ZnP@Ni 2 P and ZnP@NiSe 2 materials are confirmed by their XRD patterns in Figure S6a,b, Supporting Information, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Figures A and S6 display the representative TEM images of an individual NiSe 2 /C hybrid nanosheet from which one can see that the thin and continuous carbon nanosheets are decorated with numerous NiSe 2 nanoparticles (average size of 45 nm) and part of the neighboring NiSe 2 nanoparticles have emerged into big ones. Moreover, the abundant mesopores possessing a size of about 25 nm measured by BET (Figure S7) as distributed in the carbon nanosheet are able to facilitate the infiltration of electrolytes, shorten the ion diffusion distance, and improve the rate performance of the active materials. The corresponding selected area electron diffraction (SAED) pattern (Figure A inset) indicates that the observed spots are assigned to the crystal planes of (200), (210), and (220) of cubic phase NiSe 2 . , The HRTEM measurement (Figures C and S8) clearly shows the distinct interfaces between the formed NiSe 2 nanoparticles and amorphous carbon nanosheets inherited from the introduced glucose during the carbonization process. It is revealed that the NiSe 2 nanoparticles are closely integrated on the supporting carbon nanosheet with intimate contact, which can ensure the much enhanced structural integrity and elevated electrical conductivity of the NiSe 2 nanoparticles.…”
Section: Results and Discussionmentioning
confidence: 99%